House as Life Cycle Space in Betawi Culture, Kampung Setu Babakan - Lunggaer, Marchelia; Sihombing, Antony (International Journal of Engineering and Technology, 2019)
Betawi is the ethnic who claimed as the origin of Jakarta with many cultural activity. Betawi is the result of a mixture of many ethnic groups that produce their own culture. Until today, Betawis mostly live in the kampung which is also a place of cultural development and identity. The example of existing kampung Betawi is Setu Babakan. They inherit culture to the next generation which is by way of traditional ceremonies at every level of life cycle. Whether the architectural space that is the means of culture affect the citizens in living their lives and what changes have occurred? It is important to understand space of life cycle ceremonies. Life cycle is connection with cultural ceremonies, so in this topic I will explain the connectivity between kampung as a development space of Betawis living and life cycle as a culture, to understand how they treat their own space in kampung as their house and connectivity with each other and the modification during time.Â Â Â